O ensino da educação física em ambiente não escolar: aproximações com a abordagem crítico-emancipatória - LEÃO, João Paulo Melgueiro de Sousa (2022)
The presente work has as its central theme the approximation of the critical-emancipatory approach in dealing with bodybuilding, aiming to assist in achieving emancipation and the transformation of its relation with the practices experiences at the gym, a theme generated by the lack of critical approaches in the treatment with bodybuiloding treaining. As for the methodology, it is na action research and the data collection was made through questionnaires and subjective notes. The research shows us that it is possible to adapt a critical approach in non-school environment, presenting a new look at the practices of the physical education teachers in the gyms. We can conclude that through the critical-emancipatory approach, it is possible to work on the bodybuilding practioners, principles that awaken new concepts to relate to the world of movement and seek emancipation with regard to bodybuilding training.